Reliability and validity of a soccer passing test using the Footbonaut - Saal, C.; Zinner, J. (German Journal of Exercise and Sport Research, 2018)
The aim of this study was to investigate the reliability and validity of a soccer short passing test using the Footbonaut training system. Forty-eight young skilled soccer players and 31 lesser-skilled soccer players completed a test and a retest, each involving four sessions a day of a Footbonaut short passing test (FSPT). We found significant differences in mean execution times for skilled (mean [M]=2487, standard deviation [SD] =155) and lesser-skilled players (M=2682, SD=176) but no significant difference in accuracy (M=74.13, SD=7.65; M=72.19, SD=8.13) between groups. The results from linear mixed-effects models show that there were no significant effects of repeated measurements on execution time. In contrast, we found an estimated increase of 0.86% in accuracy per session for both groups. In conclusion, the FSPT offers a reliable and valid method to differentiate young soccer players at different competitive levels, using execution time. Ziel der vorliegenden Studie war es, die Reliabilität und Validität eines Fußballkurzpasstests unter Einsatz des Footbonaut-Trainingssystems zu prüfen. Hierfür absolvierten 48 leistungsstärkere und 31 leistungsschwächere Jugendfußballer einen Test und Retest, der jeweils vier Messreihen eines Footbonaut-Kurzpasstests pro Tag beinhaltete. Es konnten signifikante Unterschiede der mittleren Handlungszeit zwischen den leistungsstärkeren (Mittelwert [M]=2487, Standardabweichung [SD] =155) und leistungsschwächeren Spielern (M=2682, SD=176) nachgewiesen werden. Jedoch konnten keine signifianten Unterschiede in der Genauigkeit (M=74,13, SD=7,65; M=72,19, SD=8,13) zwischen den beiden Gruppen gefunden werden. Linear gemischte Modelle ergaben keine signifikanten Effekte wiederholter Messungen auf die mittlere Handlungszeit. In Bezug auf die Genauigkeit fand sich dagegen für beide Gruppen eine geschätzte Zunahme von 0,86% pro Messreihe. Zusammenfassend ist der Footbonaut-Kurzpasstest ein reliables und valides Verfahren, mit dem sich Jugendfußballer verschiedener Leistungsniveaus anhand der Ausführungszeit unterscheiden lassen.